High Efficiency Conversion of Regenerated Cellulose Hydrogel Directly to Functionalized Cellulose Nanoparticles - Wang, Han‐Qing; Tan, Huang; Hua, Sun; Liu, Zheng‐Ying; Yang, Wei; Yang, Ming‐Bo (Macromolecular rapid communications., 2017)
This article provides a novel and efficient method of “self‐assembly/modification/dispersion” for the preparation of functionalized cellulose nanoparticles (CNPs) based on regenerated cellulose hydrogel (RCH). The process of the preparation of CNPs is simplified greatly, which contributes to broadening the utilization of CNPs. Under the given conditions, cellulose chains self‐assemble into nanoparticles, which connect with each other to form strings and walls of nanoparticles inside RCH. Then, RCH acts as the hydrophilic precursor of the preparation of CNPs and is modified by oligo side chains to obtain functionalized RCH with imperfect cellulose II structures. After dispersing the functionalized RCH in dimethyl sulfoxide, individual CNPs are finally isolated from functionalized RCH as a result of the decline of the crystallinity of CNPs. Obtained CNPs possess uniform size and good thermal stability, and also exhibit excellent dispersibility in organic solvents. The particle size of CNPs can be adjusted easily by oligo content and particle size of the self‐assembled cellulose nanoparticles in RCH. Prepared CNPs are promising candidates for polymer modification in terms of fillers, and for biomedical fields with respect to drug delivery. A novel and efficient method for the preparation of functionalized cellulose nanoparticles based on regenerated cellulose hydrogel is reported in this article. This approach contains no acid hydrolysis, no solvent exchange for the functionalization, and simplifies the preparation of functionalized cellulose nanoparticles to a certain extent. Obtained functionalized cellulose nanoparticles possess excellent properties.